1980
DOI: 10.1021/bi00545a025
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence energy transfer in myosin subfragment-1

Abstract: Fluorescent probes have been selectively introduced into skeletal muscle myosin subfragment-1 and the fluorescence emission characteristics of the labeled products studied. The fluorophores employed were the thiol-specific reagents N-[[(iodoacetyl)aminolethyl-5-naphthylamine-1-sulfonic acid and 5-(iodoacetamido)fluorescein, the spectral properties of which render them a particularly effective donor-acceptor pair in Förster energy-transfer studies. Alkali 1 light chain, labeled at a single cysteine with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 58 publications
8
42
0
Order By: Relevance
“…The quantum yield of 175-IAEDANS bound to S1 in 30 mM KCl, 1.5 mM MgC12 and 20 mM Tris/HCl, pH 7.6 (buffer A) at 20°C was determined to be 0.44 in accordance with the value of 0.48 reported previously [32]. The quantum yield of FITC bound to actin in buffer A at 20 "C was determined to be 0.45 using FITC in 0.1 M NaOH as the standard which has a absolute quantum yield of 0.85 P31.…”
Section: Fluorescence Resonance Energy Transfersupporting
confidence: 87%
“…The quantum yield of 175-IAEDANS bound to S1 in 30 mM KCl, 1.5 mM MgC12 and 20 mM Tris/HCl, pH 7.6 (buffer A) at 20°C was determined to be 0.44 in accordance with the value of 0.48 reported previously [32]. The quantum yield of FITC bound to actin in buffer A at 20 "C was determined to be 0.45 using FITC in 0.1 M NaOH as the standard which has a absolute quantum yield of 0.85 P31.…”
Section: Fluorescence Resonance Energy Transfersupporting
confidence: 87%
“…A major difference between the two LCs lies in the ELC's proximity to myosin's motor domain, where the amino terminus ofthe myosin heavy chain abuts the ELC (3). This close interaction is reflected by the fact that MgATP hydrolysis in the motor domain caused a fluorophore bound to the ELC to decrease its signal with the same kinetics as the hydrolysis step (21,22). It is therefore not too surprising that ELC removal in turn affects the mechanical and kinetic properties of the myosin head.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we now know that Cys 126 is located at the interface of the RLC and the ELC; by engineering a Cys into an appropriate position on the ELC, it may be possible to detect a relative movement between the light chains upon ATP hydrolysis. It was previously shown that a probe bound to the endogenous COOH-terminal Cys of the ELC changed its fluorescence signal in parallel to the rate of myosin ATP hydrolysis (Marsh and Lowey, 1980;Marsh et al, 1982). This result is highly suggestive of a relative movement of the light chains within the neck region of myosin.…”
mentioning
confidence: 83%